Efektivitas Penggunaan Tawas dan Tanah Lempung pada Pengolahan Air Gambut Menjadi Air Bersih - Trimaily, Devita; Nofrizal, Nofrizal; Maryanti, Esy (Dinamika Lingkungan Indonesia, 2017)
Need for clean water is a very important issue and still can not be resolved, especially in the peatlands. Clean water is used for everyday purposes must comply with the requirements of water quality in accordance with the Minister of Health Decree No. 416 / Menkes / per / 1990 on the conditions and water quality control. Peat water which is a source of raw water is very abundant, whereas in the processing of peat water into clean water using a coagulant has been no literature to say exactly how many doses of coagulant used, so this research is very important to do. Therefore, this study aimed to determine the effectiveness of the use of alum, clay and a combination of both on peat water treatment. This research method using a completely randomized design-RAL (Completely Randomized Design) with two factors, alum and clay and performed repeat three times with water media processing tool is simple. Test parameters are pH, color, 6 valence chromium (Cr), manganese (Mn), iron (Fe), sulfate (SO), chloride (Cl), organic substances as KMnO4 (ZO), and hardness (CaCO3). Analysis of the data used in this study is the determination of the effectiveness of the coagulant, ANOVA test (F test) and Duncan Multiple (Duncan's Multiple Range Test). The results showed that the most effective coagulant addition is the clay of 2 g / l in combination with alum to 200 mg / l, where the combination of this coagulant obtain a pH level of 6.53 mg / l, 113.67 PtCo color, 6 valence chromium (Cr) 0,017 mg / l, manganese (Mn) 1.07 mg / l, iron (Fe) 0.39 mg / l, sulfate (SO) 108.31 mg / l, chloride (Cl) 36.56 mg / l, substance organic as KMnO4 (ZO) 90.01 mg / l, and hardness (CaCO3) 53.38 mg / l. Effectiveness and clay alum as a coagulant for peat water treatment discussed in more detail in this paper.